Sequential decarboxylative [3+2] cycloaddition and Staudinger/aza-Wittig reactions for diastereoselective synthesis of tetrahydro-pyrroloquinazolines and tetrahedro-pyrrolobenzodiazepines. Issue 2 (9th January 2020) - Ma, Xiaoming; Zhang, Xiaofeng; Awad, John Mark; Xie, Guoshu; Qiu, Weiqi; Muriph, Rachel E.; Zhang, Wei
Graphical abstract: Highlights: Decarboxylative [3+2] cycloaddition and Staudinger/aza-Wittig reactions. Diastereoselective [3+2] cycloaddition of azomethine ylides. Staudinger reaction of azides for iminophosphoranes. aza-Wittig reaction of iminophosphoranes for tetrahydro-pyrroloquinazolines and tetrahydro-pyrrolobenzodiazepines. Abstract: A method for diastereoselective synthesis of tetrahydro-pyrroloquinazolines and tetrahydro-pyrrolobenzodiazepines is developed through sequential reactions including decarboxylative 1, 3-dipolar cycloaddition of non-stabilized azomethine ylides, N -acylation or N -alkylation, and the Staudinger/aza-Wittig reactions.